Updates in Management of Ampullary Carcinomas - John, Preethi K; Kougioumtzopoulou, Andromachi S; Syrigos, Konstantinos N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Ampullary carcinomas are rare malignancies representing less than 1% of all gastrointestinal cancers. Given the low incidence rate, there is scarcity of data regarding the survival benefit of the treatment options available. In the 2014 ASCO Gastrointestinal Cancers Symposium there were two abstracts that discussed the role of pancreaticoduodenectomy and adjuvant radiation therapy in ampullary carcinoma. The first study (Abstract #366) demonstrated a decline in morbidity and mortality over time for pancreaticoduodenectomy making it a reasonable option for successful treatment of ampullary carcinoma. The second study (Abstract #282) showed that adjuvant radiation therapy in patients with T2 tumors had improved median survival times compared to patients that did not receive radiation therapy. Image: Morbidity, mortality, and survival of patients with peri-ampullary tumors who underwent pancreaticoduodenectomy (Figure 1)